Innate Immune Response in Hypertension - De Sanctis, Juan Bautista (Current pharmaceutical design, 2022)
Even though an association between inflammation and hypertension has been known for many years, it has not been simple to ascertain the role of several physiological responses involved. The innate immune response plays a critical role in these physiological responses. Innate immune cells can be activated directly by shear stress, activate the inflammasome and produce numerous cytokines and soluble mediators essential in hypertension. NFkB activation is mainly involved in the activation of innate immune cells. Shear stress also stimulates the expression of DAMP and PAMP receptors, enhancing pathogen and danger signals and magnifying inflammation. The adaptative immune response is activated with the increased antigen presentation resulting from the insults mentioned. Chronic inflammation may lead to autoimmunity. Peripheral hypoxia, a consequence of hypertension, activates hypoxia-inducing factors 1-α and 1-β (HIF-1α, HIF-1β), which modulate innate immune cells and promote inflammation. HIF-1α is involved in the upregulation of oxygen and nitrogen radical production proteins. HIF-1β down-regulates antioxidant enzymes. However, the critical evidence of the role of innate immune cells in hypertension came from the results of clinical trials involving therapies blocking inflammatory cytokines and Toll-like receptor expression. Several lines of research have been conducted on this complex disease. Pro-tolerogenic innate immune cells, myeloid suppressor cells, and M2 macrophages may play a crucial role in promoting or resolving inflammation, cardiovascular diseases and hypertension, and should be studied in detail.
Keywords: Hypertension; hypoxie; Immunity, Innate; Humans; Cytokines; Hypoxia; cytokiny; přirozená imunita; hypertenze; Inflammation; lidé; zánět